Shariah Compliance Process and Corporate Governance in Islamic Banking Institutions (IBIs): A Proposed Model - Rusnah Muhamad (Asian Journal of Accounting Perspectives, 2011)
Banking, by its very nature, entails taking a wide array of risks. One such risk is reputational risk, which arises from operational failures, i.e. failures to comply with the relevant laws and regulations, or other sources. Reputational risk is particularly damaging for banks since the nature of their business requires them to maintain the confidence of the depositors, creditors, and the general marketplace. Thus, the compliance issue is one of the most crucial factors in determining smooth and successful banking operations. Shariah compliance is a distinct feature of the Islamic banking industry. The need to have comprehensive and rigorous mechanisms in place to ensure shariah compliance as well as an effective and reliable shariah review process are the two key contributing factors for the industry to further progress. Indeed, the shariah compliance process is one of the areas upon which Islamic Banking Institutions (IBIs) must focus as part of the overall corporate governance. The purpose of this paper is to propose a shariah compliance framework for IBIs drawing from the present requirements on corporate governance (CG) in Malaysia. The framework proposes that the compliance process for IBIs is done through the internal auditing framework by establishing an internal shariah audit team. The framework proposes the Internal Shariah Audit Team (ISAT) to be a special cell of the Internal Audit Committee (IAC), which will review operations and transactions relating to shariah matters on a regular basis. The team should have bilateral functional interactions with both the IAC and the Shariah Supervisory Board (SSB).